The Dimension of Policies to Foster Employability in Higher Education - Vanna Boffo; Letizia Gamberi; Anike Odusanya; Reem Akkeila (Universidade de Lisboa, 2022)
The emphasis on graduates' employability is a significant challenge for universities to support their transitions to the labour market, especially in countries with high youth unemployment rates. The concept of employability and its main definitions constitute the framework of this paper, according to which its influence on higher education policies and practices is considered. In the context of knowledge economies and high-skilled labour demands, employability acts as an educational process that supports the transition from university to work. In this regard, the study directly addresses adult education studies, their impact on career pathways and resourcefulness in the development of a life plan. Based on this framework, the paper illustrates a comparative analysis of employability policies that influence higher education strategies in in Italy, Nigeria and Palestine.